Evaluation of the Workshop Program for Prospective Indonesian Migrant Workers in Increasing Work Competence - Dewi, Dhea Candra; Jumaah, Siti Hidayatul; Kartini, Fitriah; Benita, Novinaz (Jurnal Studi Ilmu Pemerintahan, 2023)
The Workshop on Prospective Indonesian Migrant Workers (CPMI) in East Lombok became the first program as a form of government responsibility in providing technical protection for migrant workers as mandated by law. This program has also only been running for two years, so it is necessary to evaluate the contribution and sustainability of the program. Program evaluation is a concrete step to find out whether the launched program has been realized or not. The purpose of this research is to evaluate the CPMI Workshop program in improving the competence of Indonesian Migrant Workers. The data analysis method used is concurrent embedded that focuses research on combining qualitative and quantitative research methods together. The population in this research was 80 CPMI Workshop participants. The sampling method uses saturated sampling in the form of the population of CPMI Workshop participants. Data collection uses interviews, observations, questionnaires, and documentation. The results of the study show that the CPMI workshop program at the East Lombok Job Training Center has generally been running well. This is seen from the achievement of several aspects of training evaluation using the evaluation analysis model according to Kirkpatrick which consists of reaction aspects; learning aspects; behavioral aspects; and impact aspect that shows the results that the CPMI workshop is so useful for achieving the goals that have been set.